(untitled) (Actual Problems of Mind, 2017)
The paper elucidates some characteristic features of analytic philosophy as a specific direction in modern philosophical thought. The initial point of the investigation is a definition of analytic philosophy by Michael Dummett and its critical consideration in the literature of last two decades.